'n Normatiewe benadering in die kunswetenskappe vanuit 'n wetenskapsteoretiese hoek - Duvenage, B. (Koers, 1984)
It is stated that when the Christian scholar wishes to break with the idea of norm-free science, he has to hold a different view of reality and of man, as well as of science.